Pengaruh Strategi Pemasaran Digital terhadap Minat Beli Produk di PLKT BNKP Gunungsitoli - Telaumbanua, Yukarni; mendrofa, Yupiter; Telaumbanua, Aferiaman; Laia, Otanius (The Manager Review, 2025)
This study aims to determine the influence of digital marketing strategies on consumer buying interest in PLKT BNKP Gunungsitoli. The background of this research lies in the increasing role of digital technology in business, particularly in marketing products through digital platforms such as social media. PLKT BNKP, as one of the church-owned business units in Gunungsitoli, has utilized social media—especially Facebook—for marketing activities. However, there are challenges in the effective implementation of digital strategies, which may affect consumer buying interest. This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to 60 respondents who are consumers of PLKT BNKP Gunungsitoli. Data analysis was conducted using simple linear regression and hypothesis testing with SPSS software. The results 17,3% indicate that digital marketing strategies significantly influence consumer buying interest. This is supported by the t-test results and the coefficient of determination, which show that a significant portion of the buying interest variable can be explained by the implemented digital marketing strategies. Therefore, PLKT BNKP Gunungsitoli is advised to continue developing and optimizing its digital marketing strategies to enhance consumer interest in its products.